Determinants of Live Streaming Influencing Purchase Intention for Online Computer Video Games: A Quantitative Study - Yasheen HILARIO ROMERO; Rafael O. FLORIAN-CASTRO (Communications of International Proceedings, 2022)
This research examines online video games live streaming for computers and aims to test four motivational factors for watching live broadcasts and their relationship with the intention to purchase online games. A total of 250 surveys were conducted virtually, to people who watched live video game streaming and who consumed online video games. The data of the hypotheses were processed with the statistical program Smart-PLS. The results showed that the variables knowledge acquisition, escape and social interaction influenced the intention to watch live broadcasts and that the variable intention to watch live broadcasts influenced the intention to purchase online video games; additionally, the research contributes to the proposed study model, since in previous research more variables were studied in a general way and furthermore the relationship of motivating factors and the impact they have on the intention to purchase video games through the intention to watch live broadcasts has been studied in a specific and direct way.
Keywords: Live streaming; Purchase intention; Online video games; Personal computer